Multiple Hypovascular Tumors in Kidney: A Rare Case Report and Differential Diagnosis - Pei-Yu Wu; Sheng-Fung Lin; Ping-Hsun Wu; Yi-Chun Tsai; Yu-Ting Kuo; Mei-Chuan Kuo; Hung-Chun Chen (Case Reports in Medicine)
The most common malignant renal tumor is renal cell carcinoma and surgery is the standard treatment. The proportion of lymphoma with renal involvement is 2~15% and lymphoma could be cured by chemotherapy without nephrectomy. Sonography, computed tomography (CT), and magnetic resonance imaging (MRI) can detect and characterize a renal mass. We present a case of right renal hypovascular tumors and differential diagnosis of hypovascular tumors by image study. CT scan showed hypovascular tumors and MRI image revealed multifocal hypovascular solid tumors with significantly increased apparent diffusion coefficient (ADC) of diffusion weighted imaging (DWI). Based on image finding, renal lymphoma was highly suspected. Renal lymphoma was confirmed by renal biopsy and this patient received chemotherapy without surgery. The noninvasive CT scan and MRI image can help clinicians to diagnose the characteristics of renal mass and to avoid unnecessary nephrectomy.